2016
DOI: 10.2147/ijn.s101918
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization, and evaluation of antitumor effect of Brucea javanica oil cationic nanoemulsions

Abstract: The purpose of this study was to prepare Brucea javanica oil cationic nanoemulsions (BJO-CN) with BJO as drug as well as oil phase and chitosan as cationic inducer, to explore the practical suitability of using cationic nanoemulsions for oral delivery of mixed oil, and to test its bioavailability and antitumor effect. BJO-CN was prepared by chitosan solution stirring method and then characterized physicochemically. The obtained BJO-CN had a spherical morphology with a positive zeta poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…One of the major components in the aqueous BJ extract, brusatol, is capable of overcoming drug resistance by decreasing nuclear factor erythroid 2 p45-related factor 2, thereby enhancing the cytotoxic effect of numerous chemotherapeutic agents 23. A report showed that cationic nanoemulsions of BJ oil mixture can be an effective delivery system that enhances the oral bioavailability with promising anticancer prospect 24. A recent study has proven that aqueous extract of the BJ plant suppressed the growth of liver cancer by reducing cell proliferation and activating apoptosis 14.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major components in the aqueous BJ extract, brusatol, is capable of overcoming drug resistance by decreasing nuclear factor erythroid 2 p45-related factor 2, thereby enhancing the cytotoxic effect of numerous chemotherapeutic agents 23. A report showed that cationic nanoemulsions of BJ oil mixture can be an effective delivery system that enhances the oral bioavailability with promising anticancer prospect 24. A recent study has proven that aqueous extract of the BJ plant suppressed the growth of liver cancer by reducing cell proliferation and activating apoptosis 14.…”
Section: Discussionmentioning
confidence: 99%
“…The AUC of BJO-CN was increased by 1.6-fold, and the t 1/2 was prolonged by 1.3-fold compared with BJO emulsion. CN has been demonstrated as a promising drug delivery system and has the potential to reduce the required frequency of BJO dosing 48. Genistein (Gen), an active compound found in soybeans, exerted its anticancer activity by inducing apoptosis through inhibiting tyrosine kinases and NF-κB.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, EFEN had a lower negative zeta potential (∼−1 mV), which caused it to experience less repulsion force from the negatively charged cell membrane. It has been reported that nanosystems are sometimes designed as cationic formulations in order to decrease repulsion (Liu et al., 2016 ). EFEN enhanced the mobility through cellular membranes by using liquid emulsion nanosystems that contained liquid components such as oil and surfactants (Ganta et al., 2014 ).…”
Section: Resultsmentioning
confidence: 99%